Predatory Mite, Amblyseius Swirskii (Acari: Phytoseiidae), for Biological Control of Asian Citrus Psyllid, Diaphorina Citri (Hemiptera: Psyllidae) - Juan-Blasco, María; Qureshi, Jawwad A.; Urbaneja, Alberto; Stansly, Philip A. (2017)
The Asian Citrus Psyllid (ACP), Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is a serious pest of citrus in many citrus-producing regions. It vectors the bacterium 'Candidatus Liberibacter asiaticus' thought to be the causal agent of the devastating "Huanglongbing" (HLB) or citrus greening disease. Both pest and the disease are well established in Florida. Several insect predators, particularly lady beetles and the parasitoid Tamarixia radiata (Waterston) (Hymenoptera: Eulophidae), are known to cause significant mortality to ACP immatures. However, there are no reports on the effectiveness of predatory mites against ACP. We evaluated the suitability of D. citri eggs and nymphs as prey for the predatory mite Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) in laboratory arenas, and its potential to reduce psyllid populations in the glasshouse on caged Murraya paniculata (L.) Jack plants. Mortality of D. citri eggs on M. paniculata shoots exposed to A. swirskii in plastic arenas was 4 times greater after 6 d compared to unexposed control plants. Mites were also observed sucking out body fluids of first instar nymphs. In the glasshouse, total number of D. citri adults collected over 8 wk from infested plants in ventilated cylinders with A. swirskii present averaged 80% less than the control without mites. These findings showed a significant negative impact of A. swirskii on D. citri under controlled conditions. Further research needs to focus on rates and frequency of release, impact of A. swirskii on D. citri populations in citrus and other hosts under field conditions, and interactions of A. swirskii and D. citri with native predatory mites.